APLIKASI KOMPUTER SISTEM PENUNJANG KEPUTUSAN SERTIFIKASI RESTORAN MENGGUNAKAN METODE FUZZY - Aprilia, Aina; Hermawan, Hermawan; Aries Maesya (Bajang Institute, 2024)
The Government of the Republic of Indonesia continues to strive to increase tourist visits as one of the economic drivers, one of which is by improving the quality of service. Restaurants are one of the tourism sub-sectors whose supervision is under the Ministry of Tourism and Creative Economy. Through the certification program, it is hoped that restaurants will provide excellent service quality for tourists. The Restaurant certification assessment by the Certification Business Certification Body is carried out to provide recognition status for restaurants to become stars and non-stars, based on the criteria in the Regulation of the Minister of Tourism and Creative Economy No. 14 of 2014. The assessment is carried out through direct observation of the restaurant location regarding aspects of products, services, and management which when summarized become 11 criteria. The Certification Auditor assesses using a qualitative approach to each criterion, so it may not be possible to avoid the tendency of inconsistency and subjectivity. The assessment system using a fuzzy approach allows auditors to provide values ​​between the poles of confidence and uncertainty in a criterion. The decision is made after the system calculates the fuzzy aggregation results of all defuzzyified criteria, the results are pass, conditional pass, and fail to meet the certification criteria according to stars or non-stars. Computer application for restaurant certification assessment through website is built using PHP programming. The implementation of the restaurant certification decision website is done in two stages, namely database implementation using MySQL and system implementation using Sublime Text 3. The Computer application trials have been conducted on 19 Restaurant test data in Jabotabek, The trial results are compared between the system and the auditor's manual assessment. Of the 19 test data, the system results show that 14 decisions are in accordance between the auditor's results and the system results, while the other 5 are not in accordance. Four alternatives have results that do not match between the system and manual assessment. However, the application created is considered capable of facilitating auditors in conducting field assessments.